1996
DOI: 10.1097/00005131-199610000-00008
|View full text |Cite
|
Sign up to set email alerts
|

Management of Humeral Nonunion After the Failure of Locking Intramedullary Nails

Abstract: We reviewed 21 cases of humeral nonunion following the failure of "locking" humeral nails. The nails had been inserted as the primary operative procedure following humeral fracture in fifteen cases or after the failure of closed treatment in six cases. Reconstruction after the failure of these implants was complicated by poor bone stock and difficulty in achieving union. Although technically difficult, open reduction and internal fixation with plating and bone grafting (successful in nine of nine cases) was mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
69
0
12

Year Published

2000
2000
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 129 publications
(83 citation statements)
references
References 15 publications
2
69
0
12
Order By: Relevance
“…15,[17][18][19] The purpose of our study was specifically to assess its effectiveness in treating nonunion which per- sisted despite surgical stabilisation, since such cases are notoriously difficult to treat. [10][11][12] Further surgery can put vital structures such as the radial nerve at risk. Internal fixation can be difficult because of disuse osteopenia or other bone defects.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…15,[17][18][19] The purpose of our study was specifically to assess its effectiveness in treating nonunion which per- sisted despite surgical stabilisation, since such cases are notoriously difficult to treat. [10][11][12] Further surgery can put vital structures such as the radial nerve at risk. Internal fixation can be difficult because of disuse osteopenia or other bone defects.…”
Section: Discussionmentioning
confidence: 99%
“…21,22 Exchange nailing after reaming, although successful in treating nonunion of the tibia after intramedullary nailing, 23,24 has not proved successful in the humerus. 10,22,25 five. In the ten patients who had an intramedullary nail in situ, six fractures had previously failed to unite, despite exchange nailing.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…According to some reports, the incidence of radial nerve injury in nonunion management may reach 8% with open reduction and plate fixation [10,15,18,22]. In the nine cases treated by McKnee et al [15], radial nerve injury was found in two cases. In our study, radial nerve injuries were observed in none of these cases except for the four cases with pre-existing injuries.…”
Section: Discussionmentioning
confidence: 97%
“…1,2,3,4,5,6,7 Obesity, smoking, abuse of alcohol or drugs, osteoporosis and immunodepression are additional factors that prevent bone healing. 1,4,6 Based on characteristic of the bone ends, non-unions may be atrophic, oligotrophic, and hypertrophic.…”
Section: Introductionmentioning
confidence: 99%